Post-9/11 Discourses Of Threat And Constructions Of Terror In The Age Of Obama (Altre Modernità, 2011)
We argue elsewhere (Bloodsworth-Lugo and Lugo-Lugo, 2010) that the G.W. Bush years displayed a consistent merger of discourse surrounding otherwise unrelated issues (for example, terrorism, Saddam Hussein, September 11, 2001, immigration, same-sex marriage).  This discourse served to construct and intertwine conceived international and domestic “terrorist” threats.  During Barack Obama’s campaign for the U.S presidency, post-9/11 American anxieties worked to render Obama himself into a threatening body through questions concerning his middle name (Hussein), his perceived religious affiliation, and his patriotism and citizenship.  In the present paper, we argue that the post-9/11 language of “us versus them” (“Either you are with us, or you are with the terrorists” [Bush 2001]), delivered to the American public and international community to garner consent in the wake of the September 11, 2001 events, and transformed into public policy for the remainder of the G.W. Bush presidency, provided a lens through which Americans would continue to construct and perceive the world beyond the Bush administration.  Ideology surrounding “the War on Terror,” in particular, has either been resisted or co-opted and deployed by social agents in the aftermath of September 11, 2001.  We claim that in the age of Obama, Bush-generated discourse and ideology has been activated to continue and advance policies and practices aimed at identifying and containing “terrorist” threats.